Ambulatory arterial stiffness index correlates with ambulatory pulse pressure but not dipping status in patients with grade 1/grade 2 essential hypertension. (December 2014) - Qin, Tingli; Jiang, Hong; Jiao, Yuan; Ke, Yuannan; Sun, Ningling; Wang, Jiguang; Zhu, Junren
Objective: To evaluate the relationship between ambulatory arterial stiffness index (AASI) and other parameters derived from ambulatory blood pressure (BP) monitoring, including dipping status, in patients with grade 1/grade 2 hypertension. Methods: This retrospective analysis included baseline data from Chinese outpatients enrolled into a previous study, who had clinic diastolic BP of 90–109 mmHg and systolic BP <180 mmHg, had undergone 24-h ambulatory BP monitoring and routine blood chemistry investigations, and had estimated glomerular filtration rate (eGFR) data. Results: Out of 120 patients screened, 87 were included. No significant difference in 24-h AASI was found between dippers and nondippers. The 24-h AASI significantly correlated with age, systolic BP and pulse pressure, and inversely correlated with 24-h diastolic BP variation and eGFR. In dippers and nondippers, AASI correlated with daytime pulse pressure, daytime diastolic BP variation and eGFR; in nondippers, AASI also correlated with 24-h systolic BP and 24-h pulse pressure. The 24-h AASI was significantly associated with 24-h pulse pressure and daytime pulse pressure. Conclusion: In patients with grade 1/grade 2 essential hypertension, AASI shows a significant correlation with ambulatory pulse pressure.